Relations between the Causative Factors of Waste and Their Preventive Measures in China Construction Sites - Sulala M.Z.F AL-Hamadani; Luo qing; Guilong Peng; Miaocheng Weng (International Journal of Advances in Applied Sciences, 2014)
Material waste has been considered as a major problem in the construction industry. Material waste not only has a negative impact on the success and efficiency of construction project, but also on construction cost, construction time, productivity and sustainability aspects. This paper aims to identify the major causative factors of material waste in China construction sites, their preventive measures and the relations between them. For this purpose, views of Chinese construction industry practitioners in Chongqing city were gathered by a questionnaire survey. The respondents were requested to rate a total of 34 causative factors of material waste and 9 preventive measures, which were gathered from previous literature. These causative factors were grouped into eight categories: Design, Handling, Procurement, Operation, Worker, Management, Site condition and External factors. The major causative factors of each category and preventive measures of waste were determined. Based on the identification of major factors and measures, the relations between them were also determined.